Application of metabolic modeling for targeted optimization of high seeding density processes. Issue 5 (1st March 2021) - Brunner, Matthias; Kolb, Klara; Keitel, Alena; Stiefel, Fabian; Wucherpfennig, Thomas; Bechmann, Jan; Unsoeld, Andreas; Schaub, Jochen
Abstract: Process intensification by application of perfusion mode in pre‐stage bioreactors and subsequent inoculation of cell cultures at high seeding densities (HSD) has the potential to meet the increasing requirements of future manufacturing demands. However, process development is currently restrained by a limited understanding of the cell's requirements under these process conditions. The goal of this study was to use extended metabolite analysis and metabolic modeling for targeted optimization of HSD cultivations. The metabolite analysis of HSD N‐stage cultures revealed accumulation of inhibiting metabolites early in the process and flux balance analysis led to the assumption that reactive oxygen species (ROS) were contributing to the fast decrease in cell viability. Based on the metabolic analysis an optimized feeding strategy with lactate and cysteine supplementation was applied, resulting in an increase in antibody titer of up to 47%. Flux balance analysis was further used to elucidate the surprisingly strong synergistic effect of lactate and cysteine, indicating that increased lactate uptake led to reduced ROS formation under these conditions whilst additional cysteine actively reduced ROS via the glutathione pathway. The presented results finally demonstrate the benefit of modeling approaches for process intensification as well as the potential of HSD cultivations for biopharmaceutical manufacturing. Abstract : Extended metabolite analysis in combination with flux balance analysis was applied for targeted optimization of High Seeding Density (HSD) CHO cell cultures. Flux balance analysis revealed distinct metabolic phases with high reactive oxygen species (ROS) formation and increased cell specific productivities. Based on the metabolic analysis an optimized feeding strategy with lactate and cysteine supplementation was applied leading to an increase in product titer of up to 47%.